The new authoritarianism: the crisis or the end of liberal democracy? - Vyatr, Jerzy (Journal of the Belarusian State University. Sociology, 2019)
The article presents the author’s opinion about the crisis of liberal democracy and highlights the distinction between the current crisis of liberal democracy and its previous appearances. Author considers the formation of new authoritarian regimes and defines their characteristic features. In contrast to authoritarian regimes of the last century, the strength of authoritarian regimes of the new century is based not on the use of violence, but on maintaining the electoral support. The social sources of this support are not only economic, but also cultural, and are connected to the destruction of democratic institutions. Author concludes that reforms of the institutions of representative democracy and changes in social, economic and educational policies can reduce the threat of collapse of liberal democracy.